Attitude of medical students towards learning communication skills in a medical college in Tamil Nadu - William, Roseline Fathima; Shanmugam, Jeevithan; Durairamy, Shanmugapriya (International Journal Of Community Medicine And Public Health, 2019)
Background: Effective communication plays a crucial role in establishing strong Doctor patient relationship which plays a dominant role in the treatment. Since Attitude forms the basis for the behaviour, the attitude of the students towards learning communication skills have major impact on developing effective communication skills. The objective of this study is to assess the level of attitude of medical students towards learning communication skills. Methods: A cross sectional study was conducted over 2 months among first to 4th year medical students in Karpaga Vinayaga Institute of Medical College and Research Centre, Kancheepuram using communication skills attitude scale. Data regarding the attitude and various socio demographic profile were collected through self-administered questionnaire. Hierarchical cluster analysis and K mean cluster analysis was done and Chi square test applied to find out association between the attitude and demographic variables. Results: With K mean cluster analysis, 183 students (47.9%) had high and 52.1% had moderate attitude towards learning communication skills. There is no significant association between socio demographic profiles and attitude towards learning communication skills except for the year of study and the gender. Conclusions: Overall all the students showed positive attitude towards learning communication skills, however there was decrease in level of attitude with higher the year of study.